STUDI HISTORIS ASAL-USUL NAMA KOTA SAMARINDA - Sheilla, Nanda Puspita; Sarip, Muhammad (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kota Samarinda, 2024)
Samarinda is the capital city of East Kalimantan Province which has experienced a quite long historical dynamic. The periodization of Samarinda's history began from a traditional village during the Kutai Kertanegara Empire in the 13th century to the early 18th century. Then, Samarinda became a port city that continued until the Dutch East Indies era in the 19th century to the mid-20th century. Furthermore, in the era of the Republic of Indonesia, Samarinda became the capital city of East Kalimantan Province. Although it has quite a long history, the scientific writing about the history of Samarinda City is still inadequate. One of the historical narratives that is lacking is regarding of Samarinda’s original name. The texts circulating in public about Samarinda's toponymy consist of several versions. This study aims to describe the toponymy or origin of Samarinda City’s name. This study used five stages of historical research method, namely topic determination, heuristics, verification, interpretation, and historiography. By verifying the eight versions that already found, the results of the study concluded that the name of Samarinda is a combination of the words sama and randah from the Banjar language. The basis is the geographical condition of the land surface of Samarinda which is as low as the surface of the Mahakam River that divides the city. The results of this study also strengthen previous studies that reveal the misunderstood of Samarinda City’s anniversary that based on the story of the arrival of migrants from islands outside Kalimantan. Based on the conclusions of this study, it is recommended to the Samarinda City’s Government to schedule activities and scientific forums tasked with compiling a revised manuscript of Regional Regulation Number 1 of 1988 concerning the Anniversary of Samarinda City.